A software development process model for gesture-based interface - Guimarães, Marcelo de Paiva; Martins, Valéria Farinazzo; Brega, José Remo Ferreira [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Gesture-based applications have particularities, since users interact in a natural way, much as they interact in the non-digital world. Hence, new requirements are needed on the software design process. This paper shows a software development process model for these applications, including requirement specification, design, implementation, and testing procedures. The steps and activities of the proposed model were tested through a game case study, which is a puzzle game. The puzzle is completed when all pieces of a painting are correctly positioned by the drag and drop action of users hand gesture. It also shows the results obtained of applying a heuristic evaluation on this game. © 2012 IEEE.
Keywords: Gesture Interaction; Human Computer Interaction; Human Factors; Software development; Drag and drop; Gesture interaction; Gesture-based interface; Hand gesture; Heuristic evaluation; Puzzle games; Requirement specification; Software design process; Software development process; Testing procedure; Cybernetics; Human computer interaction; Human engineering; User interfaces; Software engineering